Internal auditors' selection for sustainable competitive advantage - Ilias A.; Baidi N.; Ghani E.K. (Inderscience Publishers, 2024)
This study aimed to investigate the factors in selecting internal auditors in public listed companies (PLCs) and non-public listed companies (Non-PLCs) and the role of internal auditors. Specifically, it aimed to look at the perceptions of specific coursework and topics, students' experiential activities, and student credentials and certifications in selecting university graduates as internal auditors. In addition, this study examined the benefits of the certified internal auditor (CIA) designation for future internal auditors and the soft skills needed for the early-career of internal auditors. It found that the important factors in the selection include the course of internal audit, internship, and internal auditing experience. These factors together demonstrated communication and leadership skills. Additionally, practising internal auditors viewed the importance of the internal audit function (IAF) and foresee that the benefits of the CIA qualification would provide career advantages between PLCs and Non-PLCs and the position of internal auditors. This study could help the Institute of Internal Auditors Malaysia (IIAM) develop competent internal auditors to ensure a sustainable competitive advantage. 2023 Inderscience Enterprises Ltd.